"Can I Look Like Her?": Body Image of Adolescent Girls who Use Social Media - Sukamto, Monique; Hamidah, Hamidah; Fajrianthi, Fajrianthi (Makara Human Behavior Studies in Asia, 2019)
The use of social media is very popular among adolescents, particularly female adolescents. Social media applications that provide widespread opportunities to share photos with peers, celebrities, and families can impact the body image of adolescent girls. The aim of this study was to explore the use of social media and its impact on perceptions, cognitions, and emotions that underlie body image of adolescent girls. Furthermore, this study also explored specific behaviors as consequences of positive or negative body image of adolescent girls. The authors conducted focus group discussions on eleven first- and third-semester female students at a university in Surabaya. The results of this study showed that all participants used more than one social media application, including Line, Instagram, YouTube, WhatsApp, and Facebook. Activities these participants frequently engaged in, such as uploading photos, viewing other people’s photos, following friends or Instagram celebrities (Insta-celebs), stimulated them to make upward appearance comparisons and more likely to cause negative body image, even though there were participants who still had positive body image. Media literacy, parental guidance, and self-appreciation are necessary to overcome this problem.